SHOP FOR MOBILE PHONE APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Muhammad Syahroji; Sutarno, Skom., MMSI Sutarno, Skom., MMSI (Jurnal Sistem Informasi, 2007)
Scientific writing is about cellular phone information, equipment and also card mobile phone users by using Microsoft Visual Basic 6.0. The making of this application is intended to facilitate notification of everything on your mobile phone which is still classified as manual. Therefore, this writing is made to computerize work that is in a mobile phone store that can provide services more easily to the buyers.